Comparative efficacy and safety of mesalazine-based regimens with traditional Chinese medicines in mild-to-moderate ulcerative colitis - Huang, Bin; An, Honglin; Chen, Liming; Lin, Huimin; Wu, Huaping; Li, Ruofei; Su, Yaping; Lin, Jiumao; Shi, Dan (Frontiers in Pharmacology, 2026)
BackgroundTraditional Chinese medicine (TCM) formulations are increasingly used in combination with mesalazine to treat mild-to-moderate active ulcerative colitis (UC). However, direct comparisons between various TCM regimens are limited.MethodsWe performed a frequentist network meta-analysis of 34 randomized controlled trials (n = 2,854) comparing oral mesalazine (1.0–4.0 g/day) alone versus mesalazine plus one of eight TCM formulations: Kangfuxin solution, Shaoyao decoction, Glycyrrhizae decoction, Scutellaria decoction (Huangqin granules), Baitouweng decoction (Pulsatilla; retention enema), Shenling Baizhu Powder, CurQD formula, or Fufangkushen capsules. Outcomes included clinical efficacy, adverse events, Mayo score, serum interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), and intestinal Bifidobacteria, Lactobacilli, and Escherichia coli. Risk ratios (RRs) were calculated for dichotomous outcomes and mean differences (MDs) for continuous outcomes. Treatments were ranked using surface under the cumulative ranking curve (SUCRA).ResultsMost TCM–mesalazine combinations improved clinical efficacy versus mesalazine alone. CurQD and Kangfuxin had the highest probabilities of being most effective for symptom improvement (SUCRA 96.7% and 72.7%, respectively); the direct CurQD–mesalazine comparison showed RR = 2.67 (95% CI 1.16–6.14). Adverse-event rates were similar across regimens, with lower incidence of adverse events. Mayo score reductions were greatest with Glycyrrhizae decoction (MD = −1.40), Baitouweng decoction via retention enema (MD = −1.09), and Kangfuxin solution (MD = −1.07). Scutellaria granules produced the largest IL-6 decrease (MD = −53.28 pg/mL) and ranked highest for TNF-α reduction, followed by Kangfuxin. For gut microbiota, Shaoyao decoction ranked highest for increasing Bifidobacteria, Glycyrrhizae decoction for increasing Lactobacilli, and Glycyrrhizae also reduced E. coli (MD = −1.93).ConclusionCombining mesalazine with selected TCM formulations can enhance clinical response, reduce inflammatory cytokines, and beneficially modulate gut microbiota without increasing adverse events. CurQD or Kangfuxin may be prioritized for symptomatic improvement, Glycyrrhizae or Baitouweng for Mayo score reduction, Scutellaria for cytokine control, and Shaoyao or Glycyrrhizae for microbiota modulation. High-quality multicenter RCTs are warranted to confirm these comparative rankings.